Kecerdasan Ekologis sebagai Modal Mitigasi Bencana: Studi Krisis Lahan Tani Desa Ranupani Kabupaten Lumajang - Intan Rahmawati; Lusy Asa Akhrani (Jurnal Pengabdian Pada Masyarakat, 2020)
ECOLOGICAL INTELLIGENCE AS DISASTER MITIGATION CAPITAL: LAND CRISIS STUDY OF RANUPANI VILLAGE, LUMAJANG REGENCY. Ranupani village which is a village in Bromo Tengger Semeru National Park (TNBTS) currently has an ecological problem that needs to be considered, namely the crisis of agricultural land. Environmental awareness is a challenge for Ranupani residents to overcome the difficulties of the land caused by mistakes in planting patterns and inheritance distribution systems. Seeing this challenge, it is necessary to nurture ecological intelligence early on in order to overcome the challenges of living vulnerable to disasters. Research with qualitative considerations tries to discuss more about intelligence. The technique of collecting data using interviews with 30 Ranupani Elementary School students, observation, and literature study. This study shows Ranupani Elementary School students are still discussing ecological issues as a matter of littering and have not yet described the types of ecological problems that can cause disaster. Seeing these results, this study proves the need for early intelligence early in Ranupani Village.